Cerdas Finansial di Era Digital: Pemanfaatan Aplikasi Manajemen Keuangan Bagi Anak Yatim RW 05, 06 dan 07 Depok - Sri Rusiyati; Instianti Elyana; Ati Candrasari (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2025)
The Orphanage Assistance Agency is an agency whose members are orphans from RW 05, 06 and 07 of Pondok Cina Village, Beji District, Depok City. The purpose of the Orphanage Assistance Agency is to form students of the nation who are pious to Allah SWT, knowledgeable and have noble morals. The Orphanage Assistance Agency consists of teenagers consisting of orphans from RW 05, 06 and 07, Pondok Cina, Beji, Depok who are students from Junior High School to High School. The problem faced by the Orphanage Assistance Agency is the lack of understanding of the use of digital financial applications to manage personal finances wisely and better. This community service activity aims to develop knowledge, understanding and motivation in planning, recording, and controlling personal finances more efficiently with financial intelligence in the digital era through the use of applications for personal financial management for Orphans from RW 05, 06, and 07 Depok. The results of the study showed that there was an increase in participants by 92% in utilizing technology through the use of financial management applications, namely financial records by recording income and expenditure of funds and financial reports so that they can check the remaining funds at any time and the transition from conventional financial management to a digital-based system can be used to make long-term financial planning.